Rantai Pasok Kopra Di Desa Cio Gerong Kecamatan Morotai Selatan Barat Kabupaten Pulau Morotai - Boky, Vidya; Pakasi, Caroline Betsi Diana; Tambas, Jane Sulinda (Sam Ratulangi University, 2024)
The purpose of this study was to analyze and describe the copra supply chain in Cio Gerong Village, South West Morotai District, Morotai Island Regency. The research was conducted for 3 months, from August to November 2023. The research was conducted in Cio Gerong Village, South West Morotai District, Morotai Island Regency. This research uses primary data taken by conducting surveys, interviews, questionnaires, and documentation to respondents directly. The secondary data were taken through relevant agencies, such as the Central Bureau of Statistics, literature books, literature, journals from the internet. Sampling of farmers was done purposively (purposive sampling), the number of samples selected was 10 samples from 50 copra farmers, while the sample for copra traders was 5 people from 10 copra collectors. The data analysis used is descriptive method to identify product flow, financial flow and information flow. The results showed that the supply chain in Cio Gerong Village, West South Morotai Subdistrict, Morotai Island Regency, based on the flow of products from upstream to downstream starting from copra farmers, small collectors, and large copra collectors. The financial flow from downstream to upstream starts from large collecting traders buying copra from small collecting traders with a cash payment system and small collecting traders buying copra from farmers with a cash payment system. The flow of information flows from two directions, namely the first direction of large collectors to small collectors then to farmers, the second direction is farmers to small collectors then to large collectors.